Tenecteplase versus alteplase in bridging therapy in patients with large vessel occlusion stroke: a meta-analysis - Zhang, Xiaohan; Tao, Min; Wang, Tian; He, Rongxin; Yan, Lingwan; Lin, Xiaozuo; Wang, Pingkai; Zeng, Yinan; Yu, Jipeng; Liu, Hongxia; Luo, Man (Frontiers in Neurology, 2025)
BackgroundCurrently, for patients with large-vessel occlusion (LVO) strokes, the standard treatment approach involves using alteplase (ALT) as a bridge to endovascular mechanical thrombectomy (MT). Tenecteplase (TNK) is a novel fibrinolytic agent. Our research is focused on evaluating and comparing the efficacy and safety of TNK and ALT in patients with acute ischemic stroke (AIS) and large-vessel occlusion before they undergo MT.MethodsThe study’s research plan was registered in the International Prospective Register of Systematic Reviews (PROSPERO) under the number CRD42025643339. The entire process adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines, guaranteeing high-quality and standardized reporting and analysis.ResultsIn total, 7 studies involving 4,580 patients were incorporated. Patients treated with TNK exhibited comparable rates of functional independence at 90 days (odds ratio 1.23, 95% confidence interval 0.90–1.68, p = 0.2), post-MT recanalization (1.18, 0.93–1.51, p = 0.18), symptomatic intracerebral hemorrhage (sICH; 1.01, 0.62–1.65, p = 0.98) and mortality within 90 days (0.77, 0.51–1.18, p = 0.24) to those treated with alteplase. However, compared to alteplase-treated patients, those treated with TNK had higher rates of early recanalization (1.28, 1.06–1.53, p = 0.009), and a lower incidence of intracranial hemorrhage (ICH; 1.83, 1.26–2.66, p = 0.002).ConclusionRegarding of functional independence at 90 days, post-MT recanalization, sICH and 90-day mortality in AIS patients undergoing MT, there were essentially no difference between TNK and ALT. However, TNK might be more effective than ALT in achieving early recanalization, and it may also reduce the risks of ICH.Clinical trial registrationUnique Identifier: CRD42025643339, Publicly Accessible URL: https://www.crd.york.ac.uk/PROSPERO/.